2023
DOI: 10.1111/jne.13231
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin and glucocorticoid receptors in the prefrontal cortex are associated with anxiety‐like behavior in prenatally stressed adolescent offspring rats

Abstract: Prenatal stress (PS) causes anxiety in mothers and their offspring and chewing is a commonly observed behavior during maternal stress. Prolactin (PRL) is an anti‐anxiety factor that suppresses the hypothalamic–pituitary–adrenal axis. Here, we studied the roles of PRL, corticosterone (CORT), and their receptors in PS‐induced anxiety‐like behavior in dams and their offspring. We further investigated whether chewing during maternal stress could prevent PS‐induced harmful consequences. Pregnant rats were randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…Accumulating clinical and animal studies have demonstrated that PS raises the risk of neurodevelopmental disorders in later life periods in the offspring. For instance, offspring born to mothers who experienced stress during pregnancy have been shown to demonstrate higher anxiety levels, depression-like behaviors, and cognitive disorders in the adolescence and adulthood [1][2][3][4] . In addition, it has been shown that stressful events during pregnancy could affect the vulnerability of the offspring to addiction and drug abuse in later life 5,6 .…”
mentioning
confidence: 99%
“…Accumulating clinical and animal studies have demonstrated that PS raises the risk of neurodevelopmental disorders in later life periods in the offspring. For instance, offspring born to mothers who experienced stress during pregnancy have been shown to demonstrate higher anxiety levels, depression-like behaviors, and cognitive disorders in the adolescence and adulthood [1][2][3][4] . In addition, it has been shown that stressful events during pregnancy could affect the vulnerability of the offspring to addiction and drug abuse in later life 5,6 .…”
mentioning
confidence: 99%
“…Therefore, the release of prolactin as a response to stress is of considerable clinical importance. Several stress models have been used to characterize such effects on prolactin secretion, including ether stress [262][263][264], restraint stress [265][266][267], thermal stress [268], hemorrhage [269], social conflict [270], migraine [271], and even academic stress in humans [272,273].…”
Section: Hypothalamus Prolactin and Ptsdmentioning
confidence: 99%